Exploring the Reasons Companies Maintain a Stable Dividend Policy Amidst Earnings Fluctuations: A Qualitative Case Study Approach - Dewa Putu Yohanes Agata L. Sandopart (Varied Knowledge Journal, 2024)
This study aims to explore the reasons why companies maintain a stable dividend policy amidst earnings fluctuations using a qualitative case study approach. This phenomenon creates a puzzle in the finance literature because, theoretically, earnings fluctuations should negatively impact dividend stability. Employing an instrumental case study design on three manufacturing companies listed on the Indonesia Stock Exchange, this research interviewed ten key informants, including Finance Directors, CFOs, Financial Managers, and Commissioners, and analyzed secondary documents. Thematic analysis was employed to identify key patterns in the data. The findings generate five main themes, including commitment to signals of stability and predictability, management of shareholder expectations based on investor composition, availability of financial buffers and proactive liquidity management, governance mechanisms and agency control, and strategic considerations of policy flexibility. The results indicate that companies maintain dividend stability through three main strategies: cash reserve policies, access to credit facilities, and accumulation of retained earnings. The theoretical contribution of this research lies in enriching signaling theory and agency theory with perspectives from the emerging market context of Indonesia, as well as providing a mechanistic understanding of dividend smoothing practices.